A multi-scale approach to stress corrosion cracking - Lozano-Perez, S; English, C; Terachi, T; Yamada, T (2008)
A multi-scale approach to stress corrosion cracking has been applied to 304 type stainless steels and it is presented in this paper. The influence of cold work and chromium concentration in the alloy has been characterized. It will be shown that the same crack and, more importantly, the crack tip region can be characterized with surface techniques such as NanoSIMS and EBSD and later prepared for TEM. This will offer a unique insight into the chemistry and microstructure, proving that the right combination of techniques can provide most of the information needed to correctly understand the mechanisms of crack propagation. ©2008 by NACE International.